The Use of Thumbs-Up Emoji in Lecturer-Students' WhatsApp Communication: Qualitative Study - Cahyani, Rizka Dwi; Sahib, Rahmawansyah; Kafryawan, Wira (LPPM Universitas Bina Sarana Informatika, 2025)
This study explores Non-Verbal Online Communication in WhatsApp using the Thumbs-Up emoji, due to controversy and politeness concerns. The researcher aims to explain the implications of using Thumbs-Up emoji for EFL Lecturers and Students. This study used the Qualitative method and selected the EFL Lecturers and EFL Students of the English Study Program IAIN Fattahul Muluk Papua as participants and it took 9 participants. Data collection was by interview and online observation to answer the research questions. The data was analyzed using discourse analysis which consists of four stages; data recording, data transcription, data selection, and data interpretation. In the context of the use of the Thumbs-Up emoji in lecturer-students’ WhatsApp communication, EFL Lecturers in Papua were more dominant in using the Thumbs-Up emoji as Appreciation to EFL Students. Based on the data, the implication caused by using the Thumbs-Up emoji found two categories including feeling implication (anxious feeling and feeling rude) and situational implication (causing misunderstanding and changing the formality of conversation). Therefore, there needs a study that deepens knowledge on the use of another emojis that also often used in WhatsApp communication for Academic content.